Preparation method of aluminum silicon carbide composite material with titanium carbide as permeation promoter
By using titanium carbide as a penetration aid in the preparation of aluminum silicon carbide composite materials, the problem of poor wetting between Al and SiC is solved, and the pressure-free penetration of aluminum and the improvement of material performance is achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202410264606.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-08
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, when preparing aluminum silicon carbide composite materials, the wettability between Al and SiC is poor, resulting in a slow penetration rate during the pressureless penetration process and a longer interface reaction time, which increases the content of the brittle phase Al4C3 and affects the performance of the material.
Titanium carbide is used as a penetration aid agent, and ball milling is performed after mixing with silicon carbide to increase its contact area and reactivity with aluminum to achieve pressure-free melting of aluminum, and an aluminum silicon carbide composite material with excellent performance is prepared.
The pressure-free melting of aluminum is achieved, the mechanical properties and thermal conductivity of aluminum silicon carbide composite materials are improved, the production cost and process complexity are reduced, and it is suitable for large-scale and large-size preparations.
Smart Images

Figure CN119684003A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation, and relates to a method for preparing an aluminum silicon carbide composite material using titanium carbide as a penetration aid. Background Art
[0002] Aluminum silicon carbide composites have excellent properties such as low thermal expansion coefficient, high thermal conductivity and excellent strength, and are widely used in electronic packaging, aerospace and automobile manufacturing. At present, a series of preparation methods have been developed for the preparation of aluminum silicon carbide composites. Representative preparation methods include: powder metallurgy, stirring casting, pressure infiltration and pressureless infiltration. Although the composite materials prepared by powder metallurgy have higher performance, their sample size is small and the yield is low; the stirring casting process is simple and can be used to mass produce aluminum silicon carbide composites, but the materials prepared by it have many defects and cannot prepare materials with a high silicon carbide volume fraction; compared with pressure infiltration, pressureless infiltration is an economical and efficient near-net forming technology. However, the wettability between Al and SiC is poor, which leads to a slow penetration rate during pressureless infiltration and a prolonged interface reaction time. Therefore, this inevitably leads to the formation of brittle phase Al due to unfavorable interface reactions. 4 C 3 The content of Al 4 C 3 The presence of ions seriously affects the performance of the material.
[0003] A group of scholars have studied the pressureless infiltration of Al to prepare aluminum silicon carbide composite materials. For example, CN113800914A proposes a high-volume silicon carbide reinforced aluminum-based composite material and its preparation method and application. The invention obtains a composite by infiltrating a metal liquid with aluminum as the main component into a porous silicon carbide formed body by a pressureless or low-pressure method. The manufacturing method is characterized in that the porous silicon carbide preform is obtained by low-temperature heat treatment, and then wet deposition of copper components after multiple acid-base treatments; and the aluminum liquid is modified by adding cerium. The inventive method improves the wettability of ceramic and metal phases, and can refine the metal phase grains. However, the cerium component used in this method is relatively expensive, the process flow is complicated, and low-pressure infiltration is still required, which is not suitable for mass production of aluminum silicon carbide composite materials.
[0004] CN115161529A provides an aluminum-based silicon carbide composite material and its preparation method and application. The invention uses high-purity α silicon carbide powder composed of α silicon carbide powder with a particle size of 120-200μm, α silicon carbide powder with a particle size of 36-75μm, and α silicon carbide powder with a particle size of 8-15μm as basic raw materials, adds β silicon carbide powder, a mixture containing at least two elements of lithium, magnesium, silicon, and aluminum as a sintering aid, and adds an aqueous environmentally friendly binder as a molding aid. A porous silicon carbide skeleton (porosity 65%-75%) with uniform pores and good strength is prepared through a non-oxidative sintering process, and then pressurelessly infiltrates with aluminum alloy to prepare an aluminum-based silicon carbide composite material, the thermal conductivity can reach 250-270W / (m·K), and the thermal expansion coefficient is as low as 7.0-8.0ppm / K. However, the preparation process of this method is complicated and it is difficult to prepare large batches and large-size samples.
[0005] CN111112582B discloses a method for preparing a high-density aluminum-silicon carbide composite material, which comprises dispersing aluminum particles in silica sol, sealing and stirring, filtering and drying to obtain modified aluminum powder; mixing the obtained modified aluminum powder with alumina and kaolin and then mechanically stirring; stirring the obtained powder with silicon carbide, adding polyethylene glycol liquid and continuing to stir at a constant speed to obtain ceramic powder; pressing the ceramic powder into a molded blank, cooling it with a furnace after heat treatment to obtain a silicon carbide preform with a porosity of 30% to 40%; pressurelessly impregnating the obtained silicon carbide preform with aluminum liquid; and cooling to obtain a high-density aluminum-silicon carbide composite material. This invention not only improves the wettability of the aluminum liquid infiltration process and obtains a high-density aluminum-silicon carbide composite material, but also the generated mullite whiskers are beneficial to improving the mechanical properties of the composite material. However, the composite material prepared by this method has a slow infiltration speed and is not suitable for the production of large-size or large-volume products. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing an aluminum silicon carbide composite material using titanium carbide as a penetration aid, wherein pressureless infiltration of aluminum is achieved using titanium carbide as a penetration aid, and an aluminum silicon carbide composite material with excellent performance is prepared on the basis of economy and high efficiency.
[0007] One object of the present invention is achieved by the following technical solutions:
[0008] A method for preparing an aluminum silicon carbide composite material using titanium carbide as a penetration enhancer comprises the following steps:
[0009] Mixing raw materials including silicon carbide and titanium carbide to obtain a mixed material;
[0010] The mixed material is pressed into shape and then sintered to obtain a preform;
[0011] The preform is infiltrated with aluminum alloy without pressure to obtain an aluminum silicon carbide composite material.
[0012] Preferably, in the total volume of silicon carbide and titanium carbide, the volume fraction of titanium carbide is 0<≤50%.
[0013] More preferably, in the total volume of silicon carbide and titanium carbide, the volume fraction of titanium carbide is 0<≤30%.
[0014] Further preferably, the volume fraction of titanium carbide in the total volume of silicon carbide and titanium carbide is 2-20%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or 20%, but not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0015] Preferably, silicon carbide is in powder form, with a median particle size of 0.5 to 150 μm, more preferably 1 to 100 μm. Preferably, titanium carbide is in powder form, with a median particle size of 0.2 to 120 μm, more preferably 0.5 to 80 μm.
[0016] Preferably, the median particle size of the silicon carbide is larger than the median particle size of the titanium carbide.
[0017] More preferably, the median particle size of the titanium carbide is 1 / 2 to 1 / 15 of the median particle size of the silicon carbide.
[0018] Preferably, the purity of the silicon carbide is greater than 99%, and the purity of the titanium carbide is greater than 99%.
[0019] Preferably, the raw materials further include organic additives and pore formers. Organic additives and pore formers are commonly used in preparing porous silicon carbide preforms and are not particularly limited here. For example, the organic additives may be phenolic resin, paraffin, asphalt, polyvinyl alcohol, polystyrene, polyurethane foam, polymethyl methacrylate foam, starch, lignin, cellulose and its derivatives, etc.; the pore formers may be carbon black, graphite powder, carbon powder, diatomaceous earth, molecular sieves, etc.
[0020] The raw materials including silicon carbide and titanium carbide can be mixed by ball milling, specifically, adding the raw materials including silicon carbide and titanium carbide into a ball mill, adding anhydrous ethanol, and ball milling. For example, silicon carbide balls are used as ball milling media, the ball milling speed is 100 to 600 rpm, the ball-to-material ratio is 1 to 50:1, and the ball milling time is 0.5 to 10 hours. The slurry after ball milling is dried to obtain a mixed material.
[0021] For example, the pressure used in the press molding is 10 to 500 MPa. Further, the pressure used in the press molding can be 30 to 200 MPa.
[0022] The sintering process is a common process for preparing a silicon carbide preform and is not particularly limited here. For example, the sintering is performed in an inert atmosphere at 1400-2200° C. for 0.5-5 h.
[0023] Preferably, the pressureless infiltration is performed under an inert atmosphere, the infiltration temperature is 600 to 1300° C., and the infiltration time is 10 to 600 min. Examples of the inert atmosphere include nitrogen and argon.
[0024] More preferably, the infiltration temperature of the pressureless infiltration is 800-1200° C., and the infiltration time is 20-300 min.
[0025] The specific steps of pressureless infiltration are: placing the preform in a vacuum sintering furnace, placing aluminum alloy on the preform, and performing pressureless infiltration at 600-1300° C. for 10-600 minutes under an inert atmosphere to obtain an aluminum silicon carbide composite material.
[0026] Preferably, the aluminum alloy includes the following elements in mass fractions: Al: 90-99%, Mg: 1-10%, Zn≤0.1%, Fe≤0.05%, Si≤0.25%, O≤0.1%, and the individual content of the remaining elements is ≤0.05%, and the total content of the remaining elements is ≤0.15%.
[0027] The second object of the present invention is achieved by the following technical solutions:
[0028] An aluminum silicon carbide composite material is prepared by the above preparation method, and the aluminum silicon carbide composite material comprises silicon carbide, titanium carbide and aluminum.
[0029] Preferably, the density of the aluminum silicon carbide composite material is 2.9-3.2 g / cm 3 , further 3.0~3.1g / cm 3 , the flexural strength is 200~500Mpa, and the thermal conductivity is 100~250W / m·K.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention uses titanium carbide as a penetration aid to prepare an aluminum silicon carbide composite material, which can achieve pressureless infiltration of aluminum, and economically and efficiently prepare the aluminum silicon carbide composite material. The aluminum silicon carbide composite material finally obtained has excellent mechanical properties and thermal conductivity.
[0032] 2. Furthermore, the median particle size of the silicon carbide powder used in the present invention is larger than the median particle size of the titanium carbide powder. The aluminum silicon carbide composite material prepared by combining the large-particle-size silicon carbide powder with the small-particle-size titanium carbide powder has better performance.
[0033] 3. Furthermore, controlling the volume fraction of titanium carbide in the present invention within a suitable range is beneficial to promoting the pressureless infiltration of aluminum and giving the aluminum silicon carbide composite material more excellent performance.
[0034] 4. The preparation method of the present invention can produce aluminum silicon carbide composite materials with excellent performance in a near-net shape, thereby meeting the requirements for material performance in military, aerospace and electronic packaging, and rapidly promoting the development and large-scale use of silicon carbide composite materials in these fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is the XRD diagram of the aluminum silicon carbide composite material prepared in Example 1 of the present invention;
[0036] Figure 2 is a SEM image of the aluminum silicon carbide composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0038] In the following examples and comparative examples, the aluminum alloy blocks are made of aluminum alloy powder, and the aluminum alloy powder is purchased from Qinghe County Fengye Metal Materials Co., Ltd., and the model is 6061 aluminum powder.
[0039] The purity of silicon carbide powder is 99.9%, and the purity of titanium carbide powder is 99.9%.
[0040] Example 1
[0041] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0042] Step S1: Add silicon carbide powder with a median particle size of 5 μm and titanium carbide powder with a median particle size of 1 μm into a ball mill at a volume ratio of 19:1 for mixing, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed material.
[0043] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0044] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0045] Step S4: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 950° C. for 2 h in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0046] Figure 1 This is the XRD diagram of the aluminum silicon carbide composite material prepared in Example 1 of the present invention, and no brittle phase Al that is easily generated in the interface reaction is generated. 4 C 3 .
[0047] Figure 2 This is a SEM image of the aluminum silicon carbide composite material prepared in Example 1 of the present invention. SiC and Al are evenly distributed without obvious agglomeration. Part of SiC and Al form an interconnected network, and the formed thermal path is beneficial to improving the thermal conductivity of the material.
[0048] Example 2
[0049] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0050] Step S1: Add silicon carbide powder with a median particle size of 5 μm and titanium carbide powder with a median particle size of 1 μm into a ball mill at a volume ratio of 9:1 for mixing, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed material.
[0051] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0052] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0053] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 950° C. for 2 h in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0054] Example 3
[0055] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0056] Step S1: Add silicon carbide powder with a median particle size of 5 μm and titanium carbide powder with a median particle size of 1 μm into a ball mill at a volume ratio of 19:1 for mixing, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed material.
[0057] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0058] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0059] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 950° C. for 4 hours in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0060] Example 4
[0061] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0062] Step S1: Add silicon carbide powder with a median particle size of 50 μm and titanium carbide powder with a median particle size of 10 μm into a ball mill at a volume ratio of 19:1 for mixing, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed material.
[0063] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0064] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0065] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 950° C. for 2 h in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0066] Example 5
[0067] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0068] Step S1: Add silicon carbide powder with a median particle size of 100 μm and titanium carbide powder with a median particle size of 10 μm into a ball mill at a volume ratio of 19:1 for mixing, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed material.
[0069] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0070] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0071] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 950° C. for 2 h in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0072] Example 6
[0073] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0074] Step S1: Add silicon carbide powder with a median particle size of 5 μm and titanium carbide powder with a median particle size of 1 μm into a ball mill at a volume ratio of 9:1, mix, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven to dry, and sieved to obtain a mixed material.
[0075] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0076] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0077] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 950° C. for 4 hours in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0078] Example 7
[0079] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0080] Step S1: Add silicon carbide powder with a median particle size of 5 μm and titanium carbide powder with a median particle size of 1 μm into a ball mill at a volume ratio of 19:1 for mixing, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed material.
[0081] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0082] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0083] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 800° C. for 2 h in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0084] Example 8
[0085] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0086] Step S1: Add silicon carbide powder with a median particle size of 5 μm and titanium carbide powder with a median particle size of 1 μm into a ball mill at a volume ratio of 9:1 for mixing, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed material.
[0087] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0088] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0089] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 1000° C. for 2 h in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0090] Example 9
[0091] The preparation method of the aluminum silicon carbide composite material of this embodiment comprises the following steps:
[0092] Step S1: Add silicon carbide powder with a median particle size of 100 μm and titanium carbide powder with a median particle size of 10 μm into a ball mill at a volume ratio of 19:1 for mixing, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven for drying, and sieved to obtain a mixed material.
[0093] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0094] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0095] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 1000° C. for 0.5 h in a nitrogen atmosphere to finally obtain an aluminum silicon carbide composite material.
[0096] Example 10
[0097] The difference between Example 10 and Example 1 is that in Example 10, the median particle size of the silicon carbide powder is 1 μm, the median particle size of the titanium carbide powder is 5 μm, and the rest is the same as Example 1.
[0098] Embodiment 11
[0099] The difference between Example 11 and Example 1 is that in Example 11, the median particle size of the silicon carbide powder is 10 μm, the median particle size of the titanium carbide powder is 100 μm, and the rest is the same as Example 5.
[0100] Example 12
[0101] The difference between Example 12 and Example 1 is that the volume ratio of silicon carbide powder to titanium carbide powder in Example 12 is 4:1, and the rest is the same as Example 1.
[0102] Comparative Example 1
[0103] The difference between Comparative Example 1 and Example 1 is that no titanium carbide powder is added in Comparative Example 1, and the other steps are the same as Example 1, and the specific steps are as follows:
[0104] Step S1: Add silicon carbide powder with a median particle size of 5 μm into a ball mill, then add phenolic resin and carbon black, the mass of phenolic resin accounts for 1% of the total raw material mass, and the mass of carbon black accounts for 5% of the total raw material mass, then add anhydrous ethanol, and use silicon carbide balls as ball milling media for ball milling for 4 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 1:1. The ball-milled slurry is placed in an oven to dry, and a mixture is obtained after sieving.
[0105] Step S2: The mixed material is filled into a dry pressing mold and pressed into shape at a pressure of 50 MPa.
[0106] Step S3: The pressed green body is placed in a high-temperature horizontal vacuum sintering furnace for sintering (nitrogen atmosphere, 2000° C., sintering for 2 h) to obtain a preform.
[0107] Step S5: placing an aluminum alloy on the preform in a high-temperature horizontal vacuum sintering furnace, and performing pressureless infiltration at 950° C. for 2 h in a nitrogen atmosphere to obtain an aluminum silicon carbide composite material.
[0108] Test: Take samples of aluminum silicon carbide materials of Examples 1-12 and Comparative Example 1 with a size of 3×4×36mm, grind both sides, and test the mechanical properties using a universal material testing machine. Take samples of aluminum silicon carbide materials with a size of Φ10×3mm, grind both sides, and use a laser thermal conductivity meter to conduct experiments according to the national standard GB / 11108-89 thermal pulse method to test the thermal conductivity coefficient of the prepared aluminum silicon carbide thermal conductive material; use a direct measurement method, first use an electronic balance to weigh the mass of the skeleton reinforcement as M, then use a vernier caliper to accurately measure the length, width, and height of the cuboid, calculate the apparent volume, and calculate the volume density ρ. The test results are shown in Table 1.
[0109] Table 1 Performance data of aluminum silicon carbide materials of Examples 1-12 and Comparative Example 1
[0110]
[0111] As can be seen from Table 1, Examples 1-12 all achieved pressureless infiltration of aluminum alloys, while Comparative Example 1 lacked titanium carbide, and during pressureless infiltration at 950°C for 2 hours, the aluminum alloy did not infiltrate into the preform. This indicates that the presence of titanium carbide can be used as an infiltration aid to achieve pressureless infiltration of aluminum alloys, and the aluminum-silicon carbide composite material finally obtained has excellent mechanical properties and thermal conductivity.
[0112] The median particle size of the silicon carbide powder in Examples 10-11 is smaller than that of the titanium carbide powder, and the performance of Examples 10-11 is reduced compared with that of Examples 1 and 5. The volume ratio of silicon carbide powder to titanium carbide powder in Example 12 is 4:1, and a high content of titanium carbide powder will reduce the performance of the composite material.
[0113] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0114] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0115] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A method for preparing an aluminum silicon carbide composite material using titanium carbide as a penetration enhancer, characterized in that: The preparation method comprises the following steps: Mixing raw materials including silicon carbide and titanium carbide to obtain a mixed material; The mixed material is pressed into shape and then sintered to obtain a preform; The preform is infiltrated with aluminum alloy without pressure to obtain an aluminum silicon carbide composite material.
2. The preparation method according to claim 1, characterized in that: In the total volume of silicon carbide and titanium carbide, the volume fraction of titanium carbide is 0<≤50%.
3. The preparation method according to claim 1, characterized in that: The volume fraction of titanium carbide in the total volume of silicon carbide and titanium carbide is 2 to 20%.
4. The preparation method according to claim 1, characterized in that: Silicon carbide is in powder form, with a median particle size of 0.5 to 150 μm.
5. The preparation method according to claim 1, characterized in that: Titanium carbide is in powder form, with a median particle size of 0.2 to 120 μm.
6. The preparation method according to claim 1, 4 or 5, characterized in that: The median particle size of the silicon carbide is greater than the median particle size of the titanium carbide.
7. The preparation method according to claim 1, characterized in that: The pressureless infiltration is carried out under an inert atmosphere, the infiltration temperature is 600-1300°C, and the infiltration time is 10-600 minutes.
8. The preparation method according to claim 1, characterized in that: The aluminum alloy includes the following elements in mass fraction: Al: 90-99%, Mg: 1-10%, Zn≤0.1%, Fe≤0.05%, Si≤0.25%, O≤0.1%, the individual content of the remaining elements is ≤0.05%, and the total content of the remaining elements is ≤0.15%.
9. An aluminum silicon carbide composite material, characterized in that: The aluminum silicon carbide composite material is prepared by the preparation method according to any one of claims 1 to 8, and the aluminum silicon carbide composite material comprises silicon carbide, titanium carbide and aluminum.
10. The aluminum silicon carbide composite material according to claim 9, characterized in that: The density of the aluminum silicon carbide composite material is 2.9-3.2 g / cm 3 , the flexural strength is 200~500Mpa, and the thermal conductivity is 100~250W / m·K.
Citation Information
Patent Citations
A method for preparing high-density aluminum silicon carbide composite materials
CN111112582B
High-volume-fraction silicon carbide reinforced aluminum-based composite material as well as manufacturing method and application thereof
CN113800914A
Aluminum-based silicon carbide composite material and preparation method and application thereof
CN115161529A